The position of new activities in the factor structure of standard students' sport interests - Prot, Franjo (Array, 2003)
In this research the position of nine new activities in the factor structure of standard student's sport interests was determined. The sample of 2280 undergraduate female students was given the list of 25 well known sports and 9 activities offered to students for the first time, to be evaluated on the five-point scale. The data of 25 well known sports were analysed by confirmatory multiple-group factor analysis. The solution was determined with five following factors: (1) factor of traditional sports, defined by swimming, skiing, sports gymnastics, athletics, and cycling ; (2) team sports factor, including volleyball, basketball, football, handball, and field hockey ; (3) combat sports factor, including judo, box, taekwondo, wrestling and karate ; (4) factor of sports with marked aesthetic component, including skating, rhythmic gymnastics, dance, diving and synchronised swimming, and (5) factor of outdoor and adventurous sports, defined by scuba diving, mountaineering, watter skiing, surfing and parachuting. The evaluations of baseball, yoga, rafting, snowboard, triathlon, softball, golf, caving and crossbow were then projected in the space of five sport interests factors. Only three of "new" activities were clearly positioned. Rafting, snowboard and caving were recognized as belonging to the factor of outdoor and adventurous sports. The others, even well known from media, were not near any of five factors. Probably, to form the clear mental representation of particular sport the personal experience is needed and probably, that is the reason why students are attracted by "new" sports.